Interreligious Encounters and the Making of the Nusantara Civilization: A Comparative Reflection on Indonesia and Malaysia - Rafika Syahdina (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This paper examines how interreligious encounters shaped the Nusantara civilization through dialogue and adaptation of Islam with the beliefs that have existed before it. This research uses a qualitative and comparative approach, by studying how syncretism of religious values and cultural practices produced a pattern of religiosity which are moderate, inclusive, and related to local wisdom. This paper analyses two countries, Indonesia and Malaysia, as two inheritors of the same civilizational legacy even though they both use different ways in practicing pluralism. While Indonesia manages pluralism through Pancasila, Malaysia applied pluralism by integrating Islam in its constitution. The results show that the spirit of pluralism and religious moderation in the region is not an influence from external sources but it is an original expression of the Nusantara’s civilizational heritage which uses dialogue and humanity in their daily interaction.